Bond strength of PCC pavement repairs using metakaolin-based geopolymer mortar - Alanazi, Hani; Yang, Mijia; Zhang, Dalu; Gao, Zhili (Jerry) (Cement & concrete composites, 2016)
In order to use geopolymer mortar as a pavement repair material, a splitting test and a slant shear test are performed to characterize the bond strength of the geopolymer and conventional cement mortar interfaces. Effect of curing time, degradation of the cement mortar under different acid conditions on the bond strength of geopolymer with conventional cement mortar, and comparison of the metakaolin geopolymer with other pavement repair materials are analyzed. It was found that curing time affects the interface bond strength greatly. Metakaolin geopolymer reaches 80% of its 28 day strength in 3 days curing, but shows low strength in 24 h curing. Curing temperature affects the strength of metakaolin geopolymer, however metakaolin geopolymer cured in ambient temperature and the bond strength of 3 days curing through splitting and slant shear tests reaches 3.63 MPa and 16.32 MPa, respectively. Degradation of cement mortar negatively affects the bond strength of geopolymer and conventional cement mortar. Possibility of using metakaolin geopolymer as a repair material is discussed by comparison of this experimental result with these of other repair materials.